Heterogeneity and regulation of oligodendrocyte morphology - Osanai, Yasuyuki; Yamazaki, Reiji; Shinohara, Yoshiaki; Ohno, Nobuhiko (Frontiers in Cell and Developmental Biology, 2022)
Oligodendrocytes form multiple myelin sheaths in the central nervous system (CNS), which increase nerve conduction velocity and are necessary for basic and higher brain functions such as sensory function, motor control, and learning. Structures of the myelin sheath such as myelin internodal length and myelin thickness regulate nerve conduction. Various parts of the CNS exhibit different myelin structures and oligodendrocyte morphologies. Recent studies supported that oligodendrocytes are a heterogenous population of cells and myelin sheaths formed by some oligodendrocytes can be biased to particular groups of axons, and myelin structures are dynamically modulated in certain classes of neurons by specific experiences. Structures of oligodendrocyte/myelin are also affected in pathological conditions such as demyelinating and neuropsychiatric disorders. This review summarizes our understanding of heterogeneity and regulation of oligodendrocyte morphology concerning CNS regions, neuronal classes, experiences, diseases, and how oligodendrocytes are optimized to execute CNS functions.